Reconstruction of the Dynamics Thinking and Civilization of Khalifah Umar Bin Khattab in Islamic Education - Fadhlurrahman Fadhlurrahman; Afi Parnawi; Anaas Tri Ridlo Dina Yuliana Yuliana; Muh Alif Kurniawan (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2021)
Problems in the world of education are always in the spotlight. Because with education there will be many suitable and quality leaders. But education is not yet fully capable of forming a leader who is reliable and tough. This manuscript seeks to examine the social history of society more deeply at the time of the Caliph Umar bin Khattab and how the next generation should follow steps. He succeeded in making regulations in the world of education and issues at that time and had thoughts on problems in the world of government. This illustrates the magnitude of Caliph Umar bin Khattab's view and role in solving problems at that time. This research uses a descriptive analysis method to explain Umar bin Khattab's thoughts in Islamic education, and then the content analysis method is used to find basic ideas, development, and renewal as well as serving as caliph. For example, in education, the author found that Umar bin Khattab had thoughts about God. The discussion about God is the basis of Islamic education. They were then developed with his ideas and understanding of the cosmos (universe) to the fields of economics, law, and government so that this thought and civilization deserves to be reconstructed in the present. Keywords: Reconstruction of Civilization Islamic Education, Umar bin Khattab in Islamic Education